Electrolyte and secondary battery

By using a specific electrolyte in a lithium-ion battery to form a stable SEI film and coordination bond, the problem of poor high-temperature storage performance of lithium-ion batteries is solved, and the battery is good cycling performance and stability at room temperature are achieved.

CN120432637APending Publication Date: 2025-08-05CHERY AUTOMOBILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510597140.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-09
Publication Date
2025-08-05

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have good cycling performance at room temperature, but their high-temperature storage performance is poor and they are prone to gas failure at 60℃.

Method used

Using a specific electrolyte, including lithium salts, solvents and additives, a stable SEI film is formed on the surface of the negative electrode and a stable coordination bond is formed on the surface of the positive electrode and the surface of the lithium cobalt oxide, to inhibit the oxidation and decomposition of the electrolyte at high temperature, ensure that the cobalt in the lithium cobalt oxide complexes with the nitrile group, and avoid the residual active sites causing side reactions.

Benefits of technology

The secondary battery has achieved good circulation performance and high-temperature storage performance improvements at room temperature, ensuring that the battery does not produce gas at high temperatures and extending battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005394905530000023
    Figure BDA0005394905530000023
  • Figure BDA0005394905530000026
    Figure BDA0005394905530000026
  • Figure BDA0005394905530000027
    Figure BDA0005394905530000027
Patent Text Reader

Abstract

The invention discloses an electrolyte and a secondary battery, and belongs to the technical field of batteries. The electrolyte provided by the invention is prepared from the following components in percentage by mass: 1.0 percent to 5.0 percent of ethylene carbonate, 28.0 percent to 49.0 percent of propyl propionate, 6.0 percent to 10.0 percent of fluoroethylene carbonate, 0.5 percent to 2.0 percent of adiponitrile, 1.0 percent to 3.5 percent of 1, 3, 6-hexanetrinitrile and 0 to 1.2 percent of tris (pentafluorophenyl) borane. And the molar weight of nitrile groups in the electrolyte is greater than or equal to the molar weight of cobalt active sites on the surface of lithium cobalt oxide in the positive pole piece. The electrolyte enables the secondary battery to have good normal-temperature cycle performance and good high-temperature storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrolyte and a secondary battery. Background Art

[0002] In recent years, with the advancement of lithium-ion battery technology, lithium-ion batteries have been widely used in electric vehicles, drones, power tools and other fields.

[0003] Lithium-ion batteries in related technologies have good cycle performance at room temperature, but poor high-temperature storage performance. For example, they are prone to bloating and failure when stored at 60°C for 7 days after being fully charged. Summary of the Invention

[0004] The present invention provides an electrolyte and a secondary battery, which can make the secondary battery have both good room temperature cycle performance and good high temperature storage performance. The technical solution is as follows:

[0005] In one aspect, an electrolyte is provided, comprising: a lithium salt, a solvent, and an additive;

[0006] The lithium salt comprises the following components in mass fractions: 11.0% to 17.0% lithium hexafluorophosphate, 0% to 0.5% lithium difluorooxalatoborate, and 0% to 1.0% lithium difluorophosphate;

[0007] The solvent comprises the following components in mass fractions: 1.0% to 5.0% ethylene carbonate, 8.0% to 17.8% diethyl carbonate, 7.0% to 11.0% propylene carbonate, 28.0% to 49.0% propyl propionate, and 6.0% to 10.0% fluoroethylene carbonate;

[0008] The additive comprises the following components in mass fractions: 0-0.2% vinylene carbonate, 0.5-3.0% 1,3-propane sultone, 0.5-2.0% adiponitrile, 1.0-3.5% 1,3,6-hexanetrinitrile, 0-0.5% tris(trimethylsilyl)phosphate, and 0-1.2% tris(pentafluorophenyl)borane;

[0009] The molar amount of nitrile groups in the electrolyte is greater than or equal to the molar amount of cobalt active sites on the surface of lithium cobaltate in the positive electrode plate.

[0010] In one possible implementation, the molar amount of adiponitrile in the electrolyte is n ADN The molar amount of the 1,3,6-hexanetrinitrile is n HTCN , the molar amount of the lithium cobaltate is The actual gram capacity of the lithium cobalt oxide is The theoretical gram capacity of the lithium cobalt oxide is The ratio of the molar amount of cobalt active sites on the surface of the lithium cobalt oxide to the molar amount of the total active sites is η, n ADN 、n HTCN 、 and η satisfy the following relationship:

[0011]

[0012] In another possible implementation, the mass of the lithium cobalt oxide is The electrolyte injection coefficient is d 注液系数 , the mass fraction of adiponitrile in the electrolyte is e ADN质量分数 , the molar mass of the adiponitrile is M ADN , then n ADN 、 d 注液系数 、e ADN质量分数 and M ADN The following relationship is satisfied:

[0013]

[0014] In another possible implementation, 1 / 2 of the mean particle size of the lithium cobaltate is r, the radial number of layers of the lithium cobaltate octahedral crystal is x, the radial thickness of a single lithium cobaltate octahedral crystal is H, and 1 / 2 of the radial thickness of a single lithium cobaltate octahedral crystal is h, then η, r, x, H, and h satisfy the following relationship:

[0015]

[0016] Among them, rh-xH≥0, rh-(x+1)H<0.

[0017] In another possible implementation, the mass fraction of the ethylene carbonate is 2.0% to 5.0%;

[0018] The mass fraction of propyl propionate is 30.0-47.0%;

[0019] The mass fraction of the fluoroethylene carbonate is 6.0% to 9.6%;

[0020] The mass fraction of the tris(pentafluorophenyl)borane is 0.3% to 1.05%.

[0021] On the other hand, a secondary battery is provided, comprising: the electrolyte described in any one of the above items, a negative electrode plate, a positive electrode plate and a separator disposed in the electrolyte, wherein the negative electrode plate and the positive electrode plate are separated by the separator.

[0022] In a possible implementation, the ratio of the negative electrode reversible surface capacity to the positive electrode reversible surface capacity of the secondary battery is 1.10 to 1.25.

[0023] In another possible implementation, the positive electrode plate includes: lithium cobalt oxide, wherein the D50 of the lithium cobalt oxide is 4.0 μm to 7.0 μm;

[0024] The negative electrode plate includes: a silicon-carbon negative electrode material, and the D50 of the silicon-carbon negative electrode material is 2.0 μm to 15.0 μm.

[0025] In another possible implementation, the lithium cobalt oxide is doped with aluminum, and the amount of aluminum doping is 6000 ppm to 7000 ppm.

[0026] In another possible implementation, the mass fraction of silicon in the silicon-carbon negative electrode material is 20% to 75%.

[0027] The present application embodiment provides an electrolyte, which includes ethylene carbonate, propyl propionate, fluoroethylene carbonate and tris (pentafluorophenyl) borane, and ethylene carbonate, propyl propionate, fluoroethylene carbonate and tris (pentafluorophenyl) borane cooperate with other components to form a stable SEI (Solid Electrolyte Interface) film on the negative electrode surface, thereby improving the cycle performance of the secondary battery at room temperature. In addition, the nitrile group in adiponitrile and 1,3,6-hexane trinitrile can form a stable coordination bond with the cobalt active site on the surface of lithium cobaltate, covering its surface catalytic active point, inhibiting the oxidation and decomposition of the electrolyte at high temperature to produce gas, while the molar amount of the nitrile group is greater than or equal to the molar amount of the cobalt active site on the surface of lithium cobaltate, so as to ensure that the cobalt in the lithium cobaltate is complexed with the nitrile group, avoiding the residual active site from initiating side reactions, thereby improving the high temperature storage performance of the secondary battery. It can be seen from this that the electrolyte can make the secondary battery have both good room temperature cycle performance and good high temperature storage performance.

[0028] It should be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present disclosure. DETAILED DESCRIPTION

[0029] In order to make the technical solutions and advantages of the present application clearer, the implementation methods of the present application are described in further detail below.

[0030] In one aspect, an embodiment of the present application provides an electrolyte, the electrolyte comprising: a lithium salt, a solvent, and an additive;

[0031] The lithium salt comprises the following components in mass fractions: 11.0% to 17.0% of lithium hexafluorophosphate, 0% to 0.5% of lithium difluorooxalatoborate, and 0% to 1.0% of lithium difluorophosphate;

[0032] The solvent includes the following components in mass fractions: 1.0% to 5.0% of ethylene carbonate, 8.0% to 17.8% of diethyl carbonate, 7.0% to 11.0% of propylene carbonate, 28.0% to 49.0% of propyl propionate, and 6.0% to 10.0% of fluoroethylene carbonate;

[0033] The additive comprises the following components in mass fractions: 0-0.2% vinylene carbonate, 0.5-3.0% 1,3-propane sultone, 0.5-2.0% adiponitrile, 1.0-3.5% 1,3,6-hexanetrinitrile, 0-0.5% tris(trimethylsilyl)phosphate, and 0-1.2% tris(pentafluorophenyl)borane;

[0034] The molar amount of nitrile groups in the electrolyte is greater than or equal to the molar amount of cobalt active sites on the surface of lithium cobalt oxide in the positive electrode sheet.

[0035] The present application embodiment provides an electrolyte, which includes ethylene carbonate, propyl propionate, fluoroethylene carbonate and tris (pentafluorophenyl) borane, and ethylene carbonate, propyl propionate, fluoroethylene carbonate and tris (pentafluorophenyl) borane cooperate with other components to form a stable SEI (Solid Electrolyte Interface) film on the negative electrode surface, thereby improving the cycle performance of the secondary battery at room temperature. In addition, the nitrile group in adiponitrile and 1,3,6-hexane trinitrile can form a stable coordination bond with the cobalt active site on the surface of lithium cobaltate, covering its surface catalytic active point, inhibiting the oxidation and decomposition of the electrolyte at high temperature to produce gas, while the molar amount of the nitrile group is greater than or equal to the molar amount of the cobalt active site on the surface of lithium cobaltate, so as to ensure that the cobalt in the lithium cobaltate is complexed with the nitrile group, avoiding the residual active site from initiating side reactions, thereby improving the high temperature storage performance of the secondary battery. It can be seen from this that the electrolyte can make the secondary battery have both good room temperature cycle performance and good high temperature storage performance.

[0036] For example, the mass fraction of lithium hexafluorophosphate (LiPF6) can be 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%, 15.0%, 15.5%, 16.0%, 16.5%, 17.0%, etc. Further, the mass fraction of lithium hexafluorophosphate can be 13.0% to 16.5%.

[0037] In the embodiments of the present application, LiPF6, as the main component of lithium salt, can provide high ionic conductivity and support lithium ion insertion and extraction.

[0038] For example, the mass fraction of lithium difluorooxalatoborate (LiODFB) can be 0, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, etc. Further, the mass fraction of LiODFB can be 0.1% to 0.5%.

[0039] In the embodiments of the present application, LiODFB can form a strong SEI film on the negative electrode surface, preventing the electrolyte from decomposing on the cathode surface and corroding the carbon surface, thereby reducing side reactions and improving the cycle stability and durability of the battery. During the charging process, LiODFB can react with HF to generate stable LiDFB and LiBF4, reducing HF corrosion of the CEI film and SEI film, and reducing the dissolution and redeposition of transition metals. LiODFB can also scavenge oxygen free radicals in the electrolyte, reduce the production of oxygen and carbon dioxide, and improve the electrochemical stability of the battery. In addition, LiODFB can also improve the high temperature stability of the battery and the electrical conductivity of the electrolyte.

[0040] For example, the mass fraction of lithium difluorophosphate (LiPO2F2) can be 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1.0%. Furthermore, the mass fraction of LiPO2F2 can be 0.3% to 1.0%.

[0041] In the embodiments of the present application, LiPO2F2 can significantly reduce the interfacial impedance, increase the conductivity of the electrolyte, improve the low-temperature performance of the battery, reduce the decomposition of the electrolyte and the decomposition of the positive electrode, thereby improving the cycle stability of the battery.

[0042] For example, the mass fraction of ethylene carbonate (EC) may be 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, etc. Furthermore, the mass fraction of EC may be 2.0% to 5.0%.

[0043] In the embodiments of the present application, EC plays an important role in the electrolyte solvent system, promoting the dissociation of metal salts and forming a stable SEI film on the negative electrode surface. This is indispensable for improving the cycle performance and cycle stability of the battery. Its reduction products can also improve the stability of the electrolyte. However, due to the low oxidation potential of cyclic carbonates, a large amount of EC will be oxidized and decomposed at the positive electrode at a voltage of 4.45V to produce carbon dioxide (CO2) and carbon monoxide (CO), and reduced and decomposed at the negative electrode to produce ethylene (CH2=CH2), carbon monoxide (CO) and methane (CH4). Therefore, the mass fraction of EC in this application is limited to no more than 5.0%.

[0044] For example, the mass fraction of diethyl carbonate (DEC) can be 8.0%, 9.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 17.0%, 17.5%, 17.75%, 17.8%, etc. Further, the mass fraction of DEC can be 10.0% to 17.75%.

[0045] In the embodiment of the present application, DEC can reduce the electrolyte concentration, improve the wettability of the electrode, and reduce concentration polarization.

[0046] For example, the mass fraction of propylene carbonate (PC) may be 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, etc. Further, the mass fraction of PC may be 7.5% to 10.0%.

[0047] In the embodiment of the present application, PC has a structure similar to that of EC and has a certain negative electrode film-forming effect, which plays a certain role in improving the cycle performance of the battery.

[0048] For example, the mass fraction of propyl propionate (PP) can be 28.0%, 29.0%, 30.0%, 31.0%, 32.0%, 35.0%, 38.0%, 40.0%, 42.0%, 42.25%, 42.55%, 43.75%, 45.0%, 45.75%, 46%, 48.0%, 49.0%, etc. Further, the mass fraction of PP is 30.0% to 47.0%.

[0049] In the examples of this application, PP can form a stable SEI film on the negative electrode surface, significantly improving the ionic conductivity of the electrolyte and reducing its viscosity. It also has a high oxidation potential and does not produce gas during fully charged battery storage at 60°C. Consequently, its content is relatively high (30.0% to 47.0%).

[0050] For example, the mass fraction of fluoroethylene carbonate (FEC) may be 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, etc. Further, the mass fraction of FEC may be 6.0% to 9.6%.

[0051] In the embodiments of the present application, FEC is a negative electrode film-forming additive that can form a stable SEI film on the negative electrode surface, significantly improving the cycle performance and cycle stability of the silicon-carbon negative electrode.

[0052] For example, the mass fraction of vinylene carbonate (VC) may be 0, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, etc. Furthermore, the mass fraction of VC may be 0.04% to 0.2%.

[0053] In the embodiment of the present application, VC is a negative electrode film-forming additive that can form a stable SEI film on the negative electrode surface, reduce the side reactions of the electrolyte on the negative electrode surface, help improve the cycle stability of the battery and reduce gas generation during the charge and discharge process of the battery.

[0054] For example, the mass fraction of 1,3-propane sultone (1,3-PS) can be 0.5%, 0.7%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, etc. Furthermore, the mass fraction of 1,3-PS can be 0.7% to 2.5%.

[0055] In the embodiments of the present application, 1,3-PS is a negative electrode film-forming additive that can form a stable SEI film on the negative electrode surface, inhibiting the reduction and gas production of the electrolyte on the negative electrode surface, and helping to improve the cycle stability and high-temperature storage performance of the battery.

[0056] For example, the mass fraction of adiponitrile (ADN) may be 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, etc. Furthermore, the mass fraction of ADN may be 0.8% to 1.5%.

[0057] For example, the mass fraction of 1,3,6-hexanetricarbonitrile (HTCN) may be 1.0%, 1.2%, 1.5%, 1.6%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, etc. Furthermore, the mass fraction of HTCN may be 1.5% to 3.0%.

[0058] In the embodiments of the present application, both ADN and HTCN have nitrile groups (-C≡N), which can complex with Co in lithium cobalt oxide (LiCoO2) to form stable coordination bonds, thereby inhibiting gas production during high-temperature storage of the battery.

[0059] For example, the mass fraction of tris(trimethylsilyl)phosphate (TMSP) can be 0, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, etc. Further, the mass fraction of TMSP can be 0.05% to 0.5%.

[0060] In the embodiment of the present application, TMSP is a positive electrode film-forming additive that can undergo PO-Co complexation on the positive electrode surface to form a layer of silicate rich in lithium conductivity and electrochemically stable inorganic lithium carbonate, while also having a partial water removal effect.

[0061] For example, the mass fraction of tris(pentafluorophenyl)borane (TPFPB) can be 0, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.05%, 1.1%, 1.2%, etc. Further, the mass fraction of TPFPB can be 0.3% to 1.05%.

[0062] In the embodiment of the present application, TPFPB is a negative electrode film-forming additive, which can significantly improve the battery cycle performance in the silicon-carbon negative electrode system, and can improve the poor battery cycle performance caused by insufficient FEC content in the electrolyte system.

[0063] In an embodiment of the present application, the molar amount of nitrile groups in the electrolyte is greater than or equal to the molar amount of cobalt active sites on the surface of lithium cobaltate in the positive electrode sheet.

[0064] Among them, the nitrile groups mainly come from adiponitrile and 1,3,6-hexanetrinitrile. Adiponitrile contains two nitrile groups (-C≡N), and 1,3,6-hexanetrinitrile contains three nitrile groups (-C≡N). Therefore, the molar amount of nitrile groups in the electrolyte can be expressed as 2n ADN +3n HTCN , where n ADN represents the molar amount of adiponitrile, n HTCN represents the molar amount of 1,3,6-hexanetricarbonitrile.

[0065] The molar amount of cobalt active sites on the surface of lithium cobalt oxide can be expressed as in, It represents the molar amount of lithium cobalt oxide, in mol; Indicates the actual gram capacity of lithium cobalt oxide, in mAh / g; represents the theoretical gram capacity of lithium cobalt oxide, in mAh / g; η represents the ratio of the molar amount of cobalt active sites on the surface of lithium cobalt oxide to the molar amount of total active sites, in %.

[0066] in, It is the ratio of the amount of electricity released after the lithium cobalt oxide is fully charged to the mass of the lithium cobalt oxide. is a constant, 274 mAh / g.

[0067] Based on the above, the following relationship (1) exists:

[0068]

[0069] In one possible implementation, the molar amount of adiponitrile, n ADN It can be expressed by the following relationship (2):

[0070]

[0071] Among them, m ADN Indicates the mass of adiponitrile in g; Indicates the mass of lithium cobalt oxide in g; d 注液系数 Indicates the electrolyte filling coefficient, unit is g / Ah; e ADN质量分数 It represents the mass fraction of adiponitrile in the electrolyte, in %; M ADN It represents the molar mass of adiponitrile in g / mol.

[0072] In the embodiments of this application, It can be determined according to the mass of lithium cobalt oxide added in actual application, e ADN质量分数 0.5%~2.0%, M ADN is a constant, 108.14 g / mol, and the injection coefficient of the electrolyte is 1.7 g / Ah to 2.1 g / Ah.

[0073] For example, the electrolyte injection coefficient may be 1.7 g / Ah, 1.75 g / Ah, 1.8 g / Ah, 1.85 g / Ah, 1.9 g / Ah, 1.95 g / Ah, 2.0 g / Ah, 2.05 g / Ah, 2.1 g / Ah, etc. Further, the electrolyte injection coefficient is 1.8 g / Ah to 2.0 g / Ah.

[0074] Similarly, the molar amount of 1,3,6-hexanetrinitrile n HTCN It can be expressed by the following relationship (3):

[0075]

[0076] Among them, m HTCN Indicates the mass of 1,3,6-hexanetrinitrile in g; e HTCN质量分数 It represents the mass fraction of 1,3,6-hexanetrinitrile in the electrolyte, in %; M HTCN It represents the molar mass of 1,3,6-hexanetricarbonitrile in g / mol.

[0077] e HTCN质量分数 1.0%~3.5%, M HTCN is a constant, 161.20 g / mol.

[0078] Molar amount of lithium cobalt oxide It can be expressed by the following relationship (4):

[0079]

[0080] in, It represents the molar mass of lithium cobalt oxide in g / mol.

[0081] The ratio η of the molar amount of cobalt active sites on the surface of lithium cobalt oxide to the molar amount of total active sites can be expressed by the following relationship (5):

[0082]

[0083] Among them, rh-xH≥0, rh-(x+1)H<0.

[0084] In equation (5), r represents 1 / 2 of the mean particle size of lithium cobalt oxide, in μm; x represents the radial number of layers of lithium cobalt oxide octahedral crystals, which is a positive integer; H represents the radial thickness of a single lithium cobalt oxide octahedral crystal, in μm; h represents 1 / 2 of the radial thickness of a single lithium cobalt oxide octahedral crystal, in μm, and H=2h.

[0085] In the embodiment of the present application, r can be determined according to the particle size of lithium cobalt oxide added in actual application, and H is a constant, which is about 7×10 4 μm; x can be determined based on r and H, and then η can be determined.

[0086] In the embodiment of the present application, the adiponitrile and 1,3,6-hexanetrionitrile in the electrolyte satisfy the above relationship (1), which is beneficial to improving the cycle stability of the lithium cobalt oxide positive electrode material and inhibiting the gas generation during high-temperature storage of the battery.

[0087] On the other hand, an embodiment of the present application provides a method for preparing an electrolyte, the preparation method comprising the following steps:

[0088] Add additives to the solvent according to the mass fraction of each component, stir or shake to mix evenly, then add lithium salt, stir or shake to mix evenly to obtain an electrolyte.

[0089] Solvents include ethylene carbonate, diethyl carbonate, propylene carbonate, propyl propionate and fluoroethylene carbonate, additives include vinylene carbonate, 1,3-propane sultone, adiponitrile, 1,3,6-hexanetrinitrile, tris(trimethylsilyl)phosphate and tris(pentafluorophenyl)borane, and lithium salts include lithium hexafluorophosphate, lithium difluorooxalatoborate and lithium difluorophosphate.

[0090] When preparing the electrolyte, ethylene carbonate, diethyl carbonate, propylene carbonate, propyl propionate and fluoroethylene carbonate can be first mixed evenly, and then vinylene carbonate, 1,3-propane sultone, adiponitrile, 1,3,6-hexanetrinitrile, tris(trimethylsilyl)phosphate and tris(pentafluorophenyl)borane are added to the mixed solvent, stirred or shaken to mix evenly, and then lithium hexafluorophosphate, lithium difluorooxalatoborate and lithium difluorophosphate are added to the mixed solution, and stirred or shaken to mix evenly to obtain the electrolyte.

[0091] On the other hand, an embodiment of the present application provides a secondary battery, which includes: any of the above-mentioned electrolytes, a negative electrode plate, a positive electrode plate and a separator disposed in the electrolyte, and the negative electrode plate and the positive electrode plate are separated by the separator.

[0092] The secondary battery provided in the embodiments of the present application has all the advantages of an electrolyte and can be used in fields such as high-power drones and power tools, without specific limitation.

[0093] In one possible implementation, the positive electrode plate includes: lithium cobalt oxide, wherein the D50 of the lithium cobalt oxide is 4.0 μm to 7.0 μm;

[0094] The negative electrode plate includes: a silicon-carbon negative electrode material, and the D50 of the silicon-carbon negative electrode material is 2.0 μm to 15.0 μm.

[0095] For example, the D50 of lithium cobalt oxide may be 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, etc., and the D50 of the silicon-carbon negative electrode material may be 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm, etc. Further, the D50 of the silicon-carbon negative electrode material is 4.0 μm to 10.0 μm.

[0096] In the embodiment of the present application, the lithium cobalt oxide with a D50 of 4.0 μm to 7.0 μm has a suitable specific surface area, which can ensure that the nitrile groups in the electrolyte can fully cover the cobalt active sites, inhibit cobalt dissolution and oxygen release, thereby improving the storage performance of the battery at high temperature.

[0097] Silicon expands by as much as 300% when intercalated with lithium. Silicon-carbon anode materials with a D50 between 2.0 μm and 15.0 μm can alleviate expansion stress through the following mechanisms: (1) the internal pores of micron-sized silicon-carbon particles can accommodate some of the volume expansion; and (2) the excessive surface energy of nano-silicon (<1 μm) is avoided, which can cause severe agglomeration. Furthermore, the multi-scale particle size distribution of silicon-carbon anode materials can form an interlocking structure, improving the mechanical integrity of the electrode.

[0098] In a possible implementation, lithium cobalt oxide is doped with aluminum, and the amount of aluminum doping is 6000 ppm to 7000 ppm.

[0099] For example, the aluminum doping amount is 6000 ppm, 6100 ppm, 6200 ppm, 6300 ppm, 6400 ppm, 6500 ppm, 6600 ppm, 6700 ppm, 6800 ppm, 6900 ppm, 7000 ppm, etc. Further, the aluminum doping amount is 6300 ppm to 6800 ppm.

[0100] In the embodiments of this application, aluminum is doped into lithium cobalt oxide. Aluminum can partially replace cobalt, forming strong Al-O bonds with oxygen, significantly improving crystal field stability. Furthermore, aluminum doping can inhibit the corrosion of cobalt by HF generated by the decomposition of LiPF6 in the electrolyte, reducing the amount of cobalt dissolved, thereby improving the battery's storage performance at high temperatures. An aluminum doping level of 6000ppm to 7000ppm can balance the battery's cycle life and high-temperature storage performance.

[0101] In one possible implementation, the positive electrode plate further includes: a first conductive agent and a first binder; wherein the mass fraction of lithium cobalt oxide is 90% to 99%, the mass fraction of the first binder is 0.5% to 5%, and the mass fraction of the first conductive agent is 0.5% to 6%.

[0102] For example, the mass fraction of lithium cobalt oxide may be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, etc. Further, the mass fraction of lithium cobalt oxide may be 93% to 97%.

[0103] The mass fraction of the first binder may be 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc. Furthermore, the mass fraction of the first binder may be 0.8% to 2.5%.

[0104] The mass fraction of the first conductive agent may be 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, etc. Furthermore, the mass fraction of the first conductive agent may be 1% to 3%.

[0105] In a possible implementation, the first conductive agent is selected from at least one of conductive carbon black (SP), carbon nanotubes (CNTs), and nanofiber carbon (VGCF); and the first binder is selected from polyvinylidene fluoride (PVDF).

[0106] When preparing the positive electrode sheet, lithium cobalt oxide, a first conductive agent and a first binder can be added to the solvent, and the solid content of the positive electrode slurry can be adjusted to 50% to 70% by adjusting the amount of the solvent. Then, the positive electrode slurry is coated on the positive electrode collector and dried to obtain the positive electrode sheet.

[0107] In one possible implementation, the surface density of the positive electrode sheet is 2.0 mg / cm 2 ~22.0mg / cm 2 .

[0108] For example, the surface density of the positive electrode sheet is 2.0 mg / cm 2 、3.0mg / cm 2 , 5.0mg / cm 2 、6.0mg / cm 2 、8.0mg / cm 2 、10.0mg / cm 2 、12.0mg / cm 2 、13.0mg / cm 2 、15.0mg / cm 2 、18.0mg / cm 2 、19.0mg / cm 2 , 20.0mg / cm 2 , 21.0mg / cm 2 , 22.0mg / cm 2 Furthermore, the surface density of the positive electrode sheet is 10.0 mg / cm 2 ~18.0mg / cm 2 .

[0109] In the embodiment of the present application, setting the surface density of the positive electrode sheet in this way helps to improve the energy density of the battery.

[0110] In one possible implementation, the compaction density of the positive electrode sheet is 3.6 g / cm 3 ~3.9g / cm 3 .

[0111] For example, the compaction density of the positive electrode sheet can be 3.6 g / cm 3 、3.65g / cm 3 、3.7g / cm 3 、3.75g / cm 3 、3.8g / cm 3 、3.85g / cm 3 、3.9g / cm 3 Furthermore, the compaction density of the positive electrode sheet is 3.65g / cm 3 ~3.85g / cm 3 .

[0112] In the embodiment of the present application, the compacted density is 3.6 g / cm 3 ~3.9g / cm 3 The positive electrode sheet can improve the volume energy density of the battery.

[0113] In a possible implementation, the mass fraction of silicon in the silicon-carbon negative electrode material is 20% to 75%.

[0114] The mass fraction of silicon in the silicon-carbon negative electrode material refers to the ratio of the mass of silicon to (the mass of silicon + the mass of carbon).

[0115] For example, the mass fraction of silicon may be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, etc. Further, the mass fraction of silicon may be 30% to 60%.

[0116] In the examples of this application, when the mass fraction of silicon is less than 20%, the battery capacity gain is not significant. When the mass fraction of silicon is greater than 75%, the carbon matrix cannot effectively buffer the expansion stress, resulting in a surge in the electrode pulverization rate. Therefore, limiting the mass fraction of silicon to between 20% and 75% can both increase the battery capacity and effectively buffer the expansion stress.

[0117] In one possible implementation, the negative electrode plate also includes: a second conductive agent and a second binder, wherein the mass fraction of the silicon-carbon negative electrode (SiC) is 89% to 97%, the mass fraction of the second conductive agent is 0.5% to 6%, and the mass fraction of the second binder is 0.5% to 5%.

[0118] For example, the mass fraction of the silicon-carbon negative electrode may be 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, etc. Further, the mass fraction of the silicon-carbon negative electrode may be 89% to 95%.

[0119] The mass fraction of the second conductive agent may be 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, etc. Furthermore, the mass fraction of the second conductive agent may be 1.5% to 4.5%.

[0120] The mass fraction of the second binder may be 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc. Furthermore, the mass fraction of the second binder may be 0.5% to 2%.

[0121] In a possible implementation, the second conductive agent is selected from at least one of conductive carbon black (SP), carbon nanotubes (CNTs), and graphene; and the second binder is selected from polyacrylic acid (PAA).

[0122] When preparing the negative electrode sheet, a silicon-carbon negative electrode, a second conductive agent, and a second binder can be added to the solvent. The amount of the solvent can be adjusted to make the solid content of the negative electrode slurry 5% to 25%. The negative electrode slurry is then coated on the negative electrode collector and dried to obtain the negative electrode sheet.

[0123] The areal density of the negative electrode sheet may be the same as or different from that of the positive electrode sheet, and there is no specific limitation on this. The compaction density of the negative electrode sheet may be the same as or different from that of the positive electrode sheet, and there is no specific limitation on this.

[0124] In a possible implementation, the ratio of the negative electrode reversible surface capacity to the positive electrode reversible surface capacity of the secondary battery (reversible N / P) is 1.10 to 1.25.

[0125] in,

[0126] The mass fraction of silicon-carbon negative electrode material represents the mass fraction of silicon-carbon negative electrode material in the negative electrode plate, and the mass fraction of lithium cobalt oxide represents the mass fraction of lithium cobalt oxide in the positive electrode plate.

[0127] For example, the reversible N / P value may be 1.10, 1.11, 1.12, 1.13, 1.15, 1.16, 1.18, 1.20, 1.22, 1.24, 1.25, etc. Further, the reversible N / P value is 1.12 to 1.15.

[0128] In the embodiment of the present application, when the reversible N / P value is in the range of 1.10 to 1.25, the negative electrode has sufficient lithium insertion sites to accommodate the lithium released from the positive electrode, which will not cause lithium deposition at the negative electrode, and the battery can be reversibly charged and discharged in a cyclic manner.

[0129] In the embodiment of the present application, a certain pre-tightening force needs to be applied during battery testing, and the pre-tightening force may be 0.2 N·m to 0.8 N·m.

[0130] For example, the preload force may be 0.2 N·m, 0.3 N·m, 0.4 N·m, 0.5 N·m, 0.6 N·m, 0.7 N·m, 0.8 N·m, etc. Further, the preload force may be 0.3 N·m to 0.5 N·m.

[0131] In an embodiment of the present application, the positive electrode sheet, the negative electrode sheet and the separator can be stacked in a "Z" shape through a stacking process, and then undergo processes such as tab welding, packaging, cell baking, liquid injection, sealing, shelf infiltration, formation, secondary sealing degassing, capacity separation, aging (OCV1, OCV2), direct current internal resistance (DCIR) testing, and sorting to obtain a secondary battery.

[0132] The secondary battery provided in this application has an operating upper limit voltage of 4.45V; a 6C / 0.5C rate discharge capacity retention rate of ≥98%; a room temperature 0.5C / 3C cycle capacity retention rate of 80% with >500 cycles; no gassing after seven days of fully charged storage at 60°C; and a charge retention rate of ≥94% and a capacity recovery rate of ≥99% after 28 days of fully charged storage at room temperature. This demonstrates that the secondary battery provided in this application can simultaneously achieve both room temperature cycling performance and high temperature 60°C full charge storage performance for seven days.

[0133] The technical solution of this application will be described in detail below through specific embodiments.

[0134] In the following specific examples, operations involving conditions not specified were performed according to conventional conditions or conditions recommended by the manufacturer.

[0135] Example 1

[0136] Example 1 provides an electrolyte, see Table 1, the electrolyte includes: 16.0% LiPF6, 0.4% LiODFB, 0.4% LiPO2F2, 4.5% EC, 14.0% DEC, 8.0% PC, 43.75% PP, 9.5% FEC, 0.05% VC, 0.8% 1,3-PS, 0.9% ADN, 1.6% HTCN, 0.10% TMSP, and 0.00% TPFPB.

[0137] The preparation method of the electrolyte is as follows:

[0138] 4.5% EC, 14.0% DEC, 8.0% PC, 43.75% PP and 9.5% FEC were mixed evenly, and then 0.05% VC, 0.8% 1,3-PS, 0.9% ADN, 1.6% HTCN and 0.10% TMSP were added and mixed evenly, and then 16.0% LiPF6, 0.4% LiODFB and 0.4% LiPO2F2 were added and mixed evenly to obtain an electrolyte.

[0139] The secondary battery based on the electrolyte comprises: the electrolyte, a positive electrode sheet, a negative electrode sheet and a separator arranged in the electrolyte, wherein the positive electrode sheet and the negative electrode sheet are separated by the separator.

[0140] The positive electrode sheet includes: 95% rate-sensitive lithium cobalt oxide, 2.5% PVDF and 2.5% SP. The D50 of lithium cobalt oxide is 6μm, and the surface density of the positive electrode sheet is 15.0mg / cm 2 , compacted density is 3.8g / cm 3 .

[0141] The negative electrode sheet includes: 95% power-type silicon-carbon negative electrode material, 2% PAA and 3% CNTs. The D50 of the silicon-carbon negative electrode material is 8μm, and the ratio of silicon / (silicon + carbon) is 50%.

[0142] The reversible N / P value is 1.13, and the ratio of the molar amount of nitrile groups in the electrolyte to the molar amount of cobalt active sites on the lithium cobalt oxide surface is 1.1.

[0143] Example 2

[0144] Example 2 provides an electrolyte, see Table 1. The formula of the electrolyte can be found in Example 1, except that the mass fraction of PP is 45.75%, the mass fraction of FEC is 6.5%, and the mass fraction of TPFPB is 1.00%.

[0145] The preparation method of the electrolyte and the secondary battery based on the electrolyte can be referred to Example 1, which will not be described in detail here.

[0146] Example 3

[0147] Example 3 provides an electrolyte, see Table 1. The formula of the electrolyte can be found in Example 1, except that the mass fraction of EC is 2.5% and the mass fraction of PP is 45.75%.

[0148] The preparation method of the electrolyte and the secondary battery based on the electrolyte can be referred to Example 1, which will not be described in detail here.

[0149] Example 4

[0150] Example 4 provides an electrolyte, see Table 1. The formula of the electrolyte can be found in Example 1, except that the mass fraction of PP is 45.25% and the mass fraction of FEC is 8.0%.

[0151] The preparation method of the electrolyte and the secondary battery based on the electrolyte can be referred to Example 1, which will not be described in detail here.

[0152] Example 5

[0153] Example 5 provides an electrolyte, see Table 1. The formula of the electrolyte can be found in Example 1, except that the mass fraction of PP is 42.55% and the mass fraction of HTCN is 2.8%.

[0154] The preparation method of the electrolyte and the secondary battery based on the electrolyte can be referred to Example 1, which will not be described in detail here.

[0155] The ratio of the molar amount of nitrile groups in the electrolyte to the molar amount of cobalt active sites on the surface of lithium cobalt oxide is 1.3.

[0156] Example 6

[0157] Example 6 provides an electrolyte, see Table 1. The formula of the electrolyte can be found in Example 1, except that the mass fraction of DEC is 17.75% and the mass fraction of PP is 40.00%.

[0158] The preparation method of the electrolyte and the secondary battery based on the electrolyte can be referred to Example 1, which will not be described in detail here.

[0159] Example 7

[0160] Example 7 provides an electrolyte, see Table 1. The formula of the electrolyte can be found in Example 1, except that the mass fraction of PP is 46.75% and the mass fraction of FEC is 6.5%.

[0161] The preparation method of the electrolyte and the secondary battery based on the electrolyte can be referred to Example 1, which will not be described in detail here.

[0162] Comparative Example 1

[0163] Comparative Example 1 provides an electrolyte, see Table 2. The formula of the electrolyte can be found in Example 1 and will not be repeated here.

[0164] The preparation method of the electrolyte and the secondary battery based on the electrolyte can refer to Example 1, except that the ratio of silicon / (silicon+carbon) is 76%.

[0165] Comparative Example 2

[0166] Comparative Example 2 provides an electrolyte, see Table 2. The formula of the electrolyte can be found in Example 1 and will not be repeated here.

[0167] The preparation method of the electrolyte and the secondary battery based on the electrolyte can both refer to Example 1, except that the reversible N / P value is 1.05.

[0168] Comparative Example 3

[0169] Comparative Example 3 provides an electrolyte, see Table 2. The formula of the electrolyte can be referred to Example 1, except that the mass fraction of PP is 44.95%, the mass fraction of ADN is 0.4%, and the mass fraction of HTCN is 0.9%.

[0170] The preparation method of the electrolyte and the secondary battery based on the electrolyte can refer to Example 1, except that the ratio of the molar amount of nitrile groups in the electrolyte to the molar amount of cobalt active sites on the surface of lithium cobaltate is 0.8.

[0171] Comparative Example 4

[0172] Comparative Example 4 provides an electrolyte, see Table 2. The formula of the electrolyte can be found in Example 1, except that the mass fraction of EC is 0.5% and the mass fraction of PP is 47.75%.

[0173] The preparation method of the electrolyte and the secondary battery based on the electrolyte can be referred to Example 1, which will not be described in detail here.

[0174] Comparative Example 5

[0175] Comparative Example 5 provides an electrolyte, see Table 2. The formula of the electrolyte can be found in Example 1, except that the mass fraction of FEC is 5.0% and the mass fraction of PP is 48.25%.

[0176] The preparation method of the electrolyte and the secondary battery based on the electrolyte can be referred to Example 1, which will not be described in detail here.

[0177] Comparative Example 6

[0178] Comparative Example 6 provides an electrolyte, see Table 2. The formula of the electrolyte can be found in Example 1, except that the mass fraction of DEC is 8.25% and the mass fraction of PP is 49.5%.

[0179] The preparation method of the electrolyte and the secondary battery based on the electrolyte can be referred to Example 1, which will not be described in detail here.

[0180] Table 1

[0181]

[0182]

[0183] Table 2

[0184] Mass fraction / % Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 <![CDATA[LiPF6]]> 16.0 16.0 16.0 16.0 16.0 16.0 LiODFB 0.4 0.4 0.4 0.4 0.4 0.4 <![CDATA[LiPO2F2]]> 0.4 0.4 0.4 0.4 0.4 0.4 EC 4.5 4.5 4.5 0.5 4.5 4.5 DEC 14.0 14.0 14.0 14.0 14.0 8.25 PC 8.0 8.0 8.0 8.0 8.0 8.0 PP 43.75 43.75 44.95 47.75 48.25 49.5 FEC 9.5 9.5 9.5 9.5 5.0 9.5 VC 0.05 0.05 0.05 0.05 0.05 0.05 1,3-PS 0.8 0.8 0.8 0.8 0.8 0.8 ADN 0.9 0.9 0.4 0.9 0.9 0.9 HTCN 1.6 1.6 0.9 1.6 1.6 1.6 TMSP 0.1 0.1 0.1 0.1 0.1 0.1 TPFPB 0 1.0 0 0 0 0 sum 100 100 100 100 100 100

[0185] The present application conducted performance tests on the batteries prepared in Examples 1 to 7 and Comparative Examples 1 to 6, and the test items are as follows:

[0186] (1) Room temperature 6C / 0.5C rate performance:

[0187] At 25±2℃, place the battery on the test clamp, apply a certain preload, connect to the charge and discharge cabinet, charge to 4.45V at 0.5C constant current, then charge to 0.05C at constant voltage, leave for 30 minutes, discharge to 2.5V at 0.5C constant current, and record the 0.5C discharge capacity; leave for 30 minutes, and finally charge to 4.45V at 0.5C constant current, then charge to 0.05C at constant voltage, leave for 30 minutes, and discharge to 2.5V at 6C constant current, and record the 6C discharge capacity.

[0188] Room temperature 6C / 0.5C discharge capacity retention rate = 6C discharge capacity / 0.5C discharge capacity.

[0189] (2) Normal temperature 0.5°C / 3°C cycle performance:

[0190] At 25±2℃, place the battery on the test clamp, apply a certain preload, connect it to the charge and discharge cabinet, charge it to 4.45V with a constant current of 0.5C, then charge it to 0.05C with a constant voltage, leave it for 30 minutes, discharge it to 2.5V with a constant current of 3C, leave it for 30 minutes, repeat the above steps, record the discharge capacity of the first cycle as the initial discharge capacity Q1, record the discharge capacity of the Nth cycle as Q N , record the discharge capacity of the N+1 cycle as Q N+1 When Q N / Q1≥80% and Q N+1 When / Q1 is less than 80%, record N as the number of cycles of the battery at room temperature 0.5°C / 3°C.

[0191] (3) Performance after 7 days of full charge storage at 60°C:

[0192] At 25±2°C, place the battery on a test plate, apply a certain preload, connect it to a charge and discharge cabinet, leave it for 10 minutes, discharge it at a constant current of 0.2C to 2.5V, leave it for 30 minutes, charge it at a constant current of 0.2C to 4.45V, then charge it at a constant voltage to 0.02C, leave it for 30 minutes, discharge it at a constant current of 0.2C to 2.5V, leave it for 30 minutes, charge it at a constant current of 0.2C to 4.45V, then charge it at a constant voltage to 0.02C, and leave it for 10 minutes. Remove the battery plate and place it in a 60°C oven for 7 days. After 7 days, remove the battery from the oven and observe whether it is bloating or bulging.

[0193] (4) Performance after 28 days of full-charge storage at room temperature:

[0194] At 25±2°C, place the battery on a test clamp, apply a certain preload, connect it to a charge and discharge cabinet, leave it for 10 minutes, discharge it at a constant current of 0.2C to 2.5V, leave it for 30 minutes, charge it at a constant current of 0.2C to 4.45V, then charge it at a constant voltage to 0.02C, leave it for 30 minutes, discharge it at a constant current of 0.2C to 2.5V, leave it for 30 minutes, charge it at a constant current of 0.2C to 4.45V, then charge it at a constant voltage to 0.02C, leave it for 10 minutes, and record the battery's 0.2C initial discharge capacity. Remove the battery clamp and place it in a 25°C oven for 28 days. Remove the battery from the oven after 28 days.

[0195] Place the battery on the test clamp, apply a certain preload, connect it to the charge and discharge cabinet, leave it for 30 minutes, discharge it at a constant current of 0.2C to 2.5V, leave it for 30 minutes, charge it at a constant current of 0.2C to 4.45V, then charge it at a constant voltage of 0.02C, and leave it for 30 minutes. Repeat this process four times. Record the discharge capacity of the first cycle as the residual capacity, and the maximum value of the discharge capacity of the second, third, and fourth cycles as the recovered capacity.

[0196] Remaining capacity retention rate = (remaining capacity / initial discharge capacity) * 100%;

[0197] Recovery capacity retention rate = (recovery capacity / initial discharge capacity)*100%.

[0198] The test results are shown in Table 3.

[0199] Table 3

[0200]

[0201]

[0202] According to the test results of Example 1 and Comparative Example 1, the higher the silicon / (silicon + carbon) ratio, the worse the room temperature cycle performance of the battery. According to the test results of Example 1 and Comparative Example 2, when the reversible N / P value is lower than 1.10, the room temperature cycle performance of the battery will deteriorate. According to the test results of Example 5 and Comparative Example 3, when the molar amount of nitrile groups in the electrolyte is less than the molar amount of cobalt active sites on the surface of lithium cobalt oxide, the battery will swell when stored at 60°C for 7 days with a full charge. According to the test results of Example 3 and Comparative Example 4, the lower the mass fraction of EC, the worse the room temperature cycle performance of the battery. According to the test results of Example 4 and Comparative Example 5, the lower the mass fraction of FEC, the worse the room temperature cycle performance of the battery. According to the test results of Example 2 and Example 7, the lower the mass fraction of TPFPB, the worse the room temperature cycle performance of the battery. According to the test results of Example 6 and Comparative Example 6, the higher the mass fraction of PP, the worse the room temperature cycle performance of the battery.

[0203] The above description is only for the purpose of facilitating those skilled in the art to understand the technical solution of this application and is not intended to limit this application. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of this application shall be included in the scope of protection of this application.

Claims

1. An electrolyte, characterized in that: The electrolyte comprises: lithium salt, solvent and additives; The lithium salt comprises the following components in mass fractions: 11.0% to 17.0% lithium hexafluorophosphate, 0% to 0.5% lithium difluorooxalatoborate, and 0% to 1.0% lithium difluorophosphate; The solvent comprises the following components in mass fractions: 1.0% to 5.0% ethylene carbonate, 8.0% to 17.8% diethyl carbonate, 7.0% to 11.0% propylene carbonate, 28.0% to 49.0% propyl propionate, and 6.0% to 10.0% fluoroethylene carbonate; The additive comprises the following components in mass fractions: 0-0.2% vinylene carbonate, 0.5-3.0% 1,3-propane sultone, 0.5-2.0% adiponitrile, 1.0-3.5% 1,3,6-hexanetrinitrile, 0-0.5% tris(trimethylsilyl)phosphate, and 0-1.2% tris(pentafluorophenyl)borane; The molar amount of nitrile groups in the electrolyte is greater than or equal to the molar amount of cobalt active sites on the surface of lithium cobaltate in the positive electrode plate.

2. The electrolyte according to claim 1, characterized in that The molar amount of adiponitrile in the electrolyte is n ADN The molar amount of the 1,3,6-hexanetrinitrile is n HTCN , the molar amount of the lithium cobaltate is The actual gram capacity of the lithium cobalt oxide is The theoretical gram capacity of the lithium cobalt oxide is The ratio of the molar amount of cobalt active sites on the surface of the lithium cobalt oxide to the molar amount of the total active sites is η, n ADN 、n HTCN 、 and η satisfy the following relationship:

3. The electrolyte according to claim 2, characterized in that The mass of the lithium cobalt oxide is The electrolyte injection coefficient is d 注液系数 The mass fraction of adiponitrile in the electrolyte is e ADN质量分数 , the molar mass of the adiponitrile is M ADN , then n ADN 、 d 注液系数 、e ADN质量分数 and M ADN The following relationship is satisfied:

4. The electrolyte according to claim 2, characterized in that 1 / 2 of the average particle size of the lithium cobaltate is r, the radial number of layers of the lithium cobaltate octahedron crystal is x, the radial thickness of a single lithium cobaltate octahedron crystal is H, and 1 / 2 of the radial thickness of a single lithium cobaltate octahedron crystal is h, then η, r, x, H and h satisfy the following relationship: Among them, rh-xH≥0, rh-(x+1)H<0.

5. The electrolyte according to claim 1, characterized in that The mass fraction of the ethylene carbonate is 2.0% to 5.0%; The mass fraction of propyl propionate is 30.0-47.0%; The mass fraction of the fluoroethylene carbonate is 6.0% to 9.6%; The mass fraction of the tris(pentafluorophenyl)borane is 0.3% to 1.05%.

6. A secondary battery, characterized in that: The secondary battery comprises: the electrolyte according to any one of claims 1 to 5, a negative electrode sheet, a positive electrode sheet and a separator disposed in the electrolyte, wherein the negative electrode sheet and the positive electrode sheet are separated by the separator.

7. The secondary battery according to claim 6, characterized in that The ratio of the negative electrode reversible surface capacity to the positive electrode reversible surface capacity of the secondary battery is 1.10 to 1.

25.

8. The secondary battery according to claim 6, wherein The positive electrode plate comprises: lithium cobalt oxide, wherein the D50 of the lithium cobalt oxide is 4.0 μm to 7.0 μm; The negative electrode plate includes: a silicon-carbon negative electrode material, and the D50 of the silicon-carbon negative electrode material is 2.0 μm to 15.0 μm.

9. The secondary battery according to claim 8, characterized in that The lithium cobalt oxide is doped with aluminum, and the amount of aluminum doping is 6000ppm to 7000ppm.

10. The secondary battery according to claim 8, wherein The mass fraction of silicon in the silicon-carbon negative electrode material is 20% to 75%.